The road less traveled—Crossing gender and racial lines in comprehensive mentoring. (2015) - Kent, Andrea M.; Green, Andre M.; Feldman, Phillip
Highlights: The findings of this study yielded four identifiable developmental stages. The obvious implications of race and gender were respected and embraced. Trust and the commitment to the relationship were critical for success. A clearly understood purpose of the relationship makes a long-term difference. Abstract: The purpose of this study was to examine the induction process of two professors, with specific emphasis on mentoring, from entering assistant professors through their journey of tenure and promotion, and beyond. A Caucasian male professor with 40 years experience in higher education engaged in the induction process with a Caucasian female and an African-American male over the course of 10 years and 8 years, respectively. The participant researchers sought to determine if a longitudinal induction program that relied heavily upon mentoring yielded successful results, especially in the context of cross-cultural mentoring. The study operationalizes critical reflection centered on participants' collaborations and shared norms, values, and practices resulting in four stages of induction.